ANALISIS TINGKAT PEMAHAMAN AKUNTANSI SERTA PERAN INTERNAL AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN KEPULAUAN MENTAWAI - Eldinus Samongilaila; Muhammad Rosidi (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This study aims to determine: (1) the effect of the level of understanding of accounting on the quality of the financial statements of the local government of the Mentawai Islands Regency. (2) The influence of the role of internal audit on the quality of the financial statements of the local government of the Mentawai Islands Regency. This type of research is causative research. The population is 15 Regional Apparatus Work Units (SKPD) of the Mentawai Islands Regency. The sampling technique is the total sampling method. Techniques Data analysis using multiple linear regression. The results showed that: (1) The level of accounting understanding had a significant positive effect on the quality of the financial statements of the local government of the Mentawai Islands Regency. (2) The role of internal audit has a significant positive effect on the quality of the financial statements of the local government of the Mentawai Islands Regency. Suggestions in apat continue to be improved. (2) The next research can expand the research variables by adding the variables of this research, namely: (1) For government agencies it is better to conduct a review of the understanding of accounting, as well as the role of internal audit in making financial reports so that the quality of financial reports from the government and other.